Requirement of major nutrients for' Alphonso' mango (Mangifera indica) - REDDY, Y T N; KURIAN, R M; KOHLI, R R; RAO, G S; RAMACHANDER, P R; GORAKHSINGH, GORAKHSINGH (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted from 1977 to 1991 to determine the nutritional requirements of 'Alphonso' mango (Mangifera indica L.) under rainfed conditions employing second order rotatable design. The results indicated little influence of the continuous application of major nutrients on tree growth and fruit quality. About 100 g N, 170 g P2 O5 and 80 g K2 O/tree/year of tree age from 3rd to 10th orchard years and continuation of the 10th year dose in subscquent years was found to be optimum for maximising the fruit yield. Since it was uneconomical to apply such high doses of phosphorus, other approaches were employed for the interpretation of the results. Second order equations involving preceding year's fruit yield in addition to the nutritional effects were found useful to suggest precise nutrient recommendations for trees of different ages. Game theory analysis suggested nutrient recommendations for various categoties of farmers based on the risk taking capacity. A nutrient dose comprising of 100 g N and 100 g K2 O/tree/year of tree age from 3rd and 10th orchard years and continuation of the 10th year dose thereafter was found to give maximum per cent returns over investment for all categories of farmers, irrespective of their risk taking abilities.